Card Sort Method: improve elementary school students early reading skills - Anggy Anggy Giri Prawiyogi; Sri Wulan Anggraeni; Lusiana Rahmatiani; Laras Nanda Milftaloka (Mimbar Ilmu, 2023)
Students' initial reading skills or abilities could be stronger. Some students need to be fluent in reading and understand the function of punctuation marks. Some students must learn the alphabet and need help seeing the difference between the letters b and d, p and q. This study aims to analyze the effect of the card sort method on the beginning reading ability of grade II elementary school students. This research belongs to the type of quantitative research using experimental methods. The population in this study were 48 grade II elementary school students. This study's sample consisted of 24 students who functioned as experimental classes using the Crd Sort Learning method and 24 as control classes who did not use the card sort method. The data collection technique used in this study was a preliminary reading test, with the research instrument being an oral reading commencement test. The research data were then analyzed using descriptive statistical analysis techniques and a t-test (Independent sample t-test). The results showed that the average pretest score for the experimental class was 51.50 and that for the control class was 55.67. After the learning treatment was carried out using the card sort method, the results of data analysis in the Posttest experimental class were an average of 83.17 and a control score with an average of 69.33. Based on the hypothesis test, it shows that the significant value (2-tailed) is 0.000. Because the significant value (2-tailed) is 0.000 < α = 0.05, Ho is rejected, and H1 is accepted, meaning there is a difference between the card sort method and students' beginning reading abilities. Class II with classes that do not use the card sort method. Based on these results, it can be concluded that the card sort method can improve students' beginning reading skills in class II.